ISLAMIC LAW REVIEW OF SHARIA FINANCING SCHEMES AT THE ELECTRIC EMPLOYEE COOPERATIVE OF SUBULUSSALAM CITY, INDONESIA - Prasetia, Agung; Tarmizi Jakfar; Dhaifina Fitriani (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This paper aims to examine three main aspects related to sharia financing at the State electricity company (Perusahaan Listrik Negara PLN) First, what sharia financing is often used in the KOKARLIS cooperative. Second, what are the challenges and obstacles that occur in the management of Islamic financing in cooperatives (KOKARLIS). Third, and how is the legal review in the practice of Islamic financing in cooperatives (KOKARLIS).  To answer these three aspects, this research uses a qualitative approach with a descriptive-analytical method. Data collection is done through primary data obtained through interviews, observation, and documentation, as well as secondary data sourced from related references. The results showed that mudharabah and murabahah contracts are the most commonly used types of financing. However, the lack of understanding of cooperative managers, who are mostly PLN employees, is the main challenge, along with the lack of training related to Islamic financing. From the perspective of Islamic law, practices that are not in accordance with sharia rules have the potential to cause gharar, which is contrary to the principle of justice in muamalah. This research emphasizes the importance of increasing the capacity of cooperative managers through continuous training and education related to the principles and practices of Islamic financing. With a better understanding, it is expected that Koperasi KOKARLIS can eliminate the risk of sharia deviations, increase member confidence, and become a better model of sharia financial management.